Salen–scandium(III) complex-catalyzed asymmetric (3 + 2) annulation of aziridines and aldehydes - Wang, Linqiang; Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2025)
Oxazolidine is one of the crucial structural moieties of biologically active compounds. A salen–scandium triflate complex-catalyzed asymmetric (3 + 2) annulation of dialkyl 1-sulfonylaziridine-2,2-dicarboxylates and aldehydes generated optically active functionalized oxazolidine derivatives in moderate to good yields and good to excellent enantioselectivities and high diastereoselectivities. A reasonable reaction mechanism was proposed and rationalized the experimental results.
Keywords: aldehyde; annulation; aziridine; oxazolidine; ring expansion; scandium triflate